Comparison of seismic responses of a jumbo-size container crane retrofitted with braces, dampers, and isolation systems. (15th October 2022) - Meisuh, Bismark Kofi; Huh, Jungwon; Haldar, Achintya; Kim, In-Tae
Abstract: The effectiveness of six seismic retrofitting intervention schemes on an existing jumbo-size container crane is investigated. They include the use of conventional steel braces and buckling-restrained braces, fluid viscous dampers and friction dampers, lead rubber bearing isolators, and natural rubber bearing isolators with viscous dampers. The six schemes can be grouped under three main strategies, i.e., the use of different types of bracings, dampers, and isolation systems. Nonlinear response history analyses, using eight spectrally matched ground motions, were conducted on 3D models of the crane, with and without any upgrading, using SAP 2000. The results showed that with the exception of the conventionally braced crane, which produced inconclusive responses, the other two retrofitting strategies of using different types of dampers and isolation systems significantly reduced the critical seismic responses of the crane. At a target drift of one-third the original, the damping systems caused on average reduction of approximately 32%, 36%, and 98% in the base shear, stress, and uplift responses, respectively. Moreover, a significant reduction of about 65% in the stress and base shear responses and a condition of no uplift were recorded when the isolation systems were applied. The results of this study show that the isolation systems produce the best performance and therefore can be considered as the most effective seismic retrofitting technique. Highlights: Vulnerability issues regarding container cranes are addressed by proposing upgrade systems to improve their performance. The behavior of a jumbo-size crane in all its working conditions is well simulated and comprehensively studied in this paper. The proposed retrofit systems are effective in reducing the seismic demand on the crane.